Judicialização da saúde: aspectos processuais e institucionais na efetivação do direito à saúde pública no estado do Tocantins - Farias, Dorane Rodrigues (Universidade Federal do Tocantins, 2016)
Heath is a fundamental social right and, according to the article 196 of the Brazilian Constitution, is a right of everyone and a State's responsibility. The public health attendance in Brazil is implemented by SUS (Sistema Único de Saúde) which is responsible to make sure to everyone the right of a free, universal and full health. Howerer the state’s financial and administrative omission and inefficiency made people search the judiciary to obtain their fundamental rights expressly consecrate in Brazilian Federal Constituion. The access to the judiciary to get the right of health increased year by year and this process received the name judicialization of health. This process is not only a judiciary's concern, which is obligated to get involved in public politics, but is also a concern of institutions and government agencies. The Supremo Tribunal Federal and the Conselho Nacional de Justiça adopted some measures to support the magistrates' decisions and reduce the number of processes related to the health assistance. So the present research titled " Judicializaton of health: Procedural and institutional aspects to obtain the right to the health public in Tocantins" will analyze the phenomena of judicialization of health emphasizing the institutional and procedural aspects that involve the guarantee of the public health's right in Tocantins.